Effect of Potassium Peroxodisulphate and Microwave Power on Hydrogel Character Based on Banana Peel Waste Using Microwave Grafting Method - Distantina, Sperisa; Anggreini, Ghea Safiraventa; Al Kamal, Fahrul An'nas; Kaavessina, Mujtahid; Fadilah, Fadilah (Equilibrium Journal of Chemical Engineering, 2023)
ABSTRACT. Musa paradisiaca var. raja peel waste contains cellulose which has the potential to be a raw material for synthesizing hydrogels. This research utilizes acrylamide monomer grafted onto banana peel cellulose backbone using the microwave grafting method to produce hydrogel. The banana peel waste was dried to a constant weight and then crushed into powder. Banana peel powder was through a delignification process with the addition of NaOH and bleached with NaClO to took only the cellulose of the banana peel. The mixture of banana peel cellulose-acrylamide-potassium peroxodisulfate powder through the grafting process was repeated with variations in KPS concentration and microwave power. The reaction was terminated with a hydroquinone solution, washed with acetone, and then precipitated. The precipitated solid was dried to a powder called cellulose-g-PAAM. A homogeneous solution of 2% carrageenan-cellulose-g-PAAM underwent a physical crosslinking process using KCl and CaCl2 solutions after passing through palm oil to form a bead gel. The purpose of this research was to determine the effect of potassium peroxodisulfate (KPS) initiator concentration and microwave power on the swelling capacity in water. The properties of obtained dried bead gels were characterized their functional groups using FTIR and swelling capacity test in water. From this research, it can be concluded that banana peel cellulose was successfully grafted onto acrylamide monomer as evidenced by the FTIR test results. The lower KPS concentration is the greater on the swelling capacity and the microwave power has no effect on the swelling capacity of bead gels.Keywords: Banana peel, Bead gel, Microwave, Swelling degree